Degradabilidad ruminal de forrajes y alimentos concentrados y estimación del consumo - Contreras P., José L. (2020)
The aim of this study was to determine the kinetic parameters of in situ degradation of dry matter (MS), crude protein (PC) and neutral detergent fibre (NDF) of four single or mixed forages: 1) alfalfa; 2) alfalfa-red clover; 3) alfalfa-dactylis; 4) oats, and two concentrates: cotton paste and ground barley, as well the estimation of the DM consumption of these forages using three cattle with ruminal fistula. Five grams of sample were incubated for 4, 8, 12, 24, 48, 72 and 96 hours for forages and 2, 4, 8, 12, 24 and 48 hours for concentrates. The zero time (t0) was used to calculate the soluble fraction. The potential and effective degradability at the 2, 5 and 8%/h passages rates of the MS, PC and NDF were different for forages and concentrates. The constant degradation rates (c) of the PC of the association alfalfa-dactylis, oats (fodder), cotton paste and ground barley indicate that these resources had good potential for ruminant diet use. Due to the effective degradability of the PC at the rates of 2, 5 and 8%/h, the forages alone or associated and the concentrates under study can be classified as feeds of high nutritional quality.